Effectiveness of Simulators in the Training of Nursing Students - Paulina Briones Bermeo, Narciza; Georgina Bravo Bonoso, Delia; del Rocío Menéndez Pin, Tania; Yamara Zambrano Loor, Liricis; de los Ángeles Moreno Cobos, Maria; Alejandra Castillo-Merino, Yasmin; De Los Ángeles Zambrano, Delia (Journal of Neonatal Surgery, 2025)
Simulation facilitates the acquisition of skills in the health field, providing a safe environment to practice before real contact with patients. Methodology: This research follows a qualitative approach and a descriptive methodology, using a non-experimental design and a documentary-bibliographic analysis. It is based on a systematic examination of scientific works related to the topic, exploring written documents, theses and scientific articles as primary sources in the study population. Conclusion: Simulation stands out in optimal conditions with constant feedback, revealing its importance in nursing education. Teacher training in simulators and technologies is emphasized. Although beneficial, simulators have limitations, such as wear and tear and lack of exact replication of real situations. Virtual simulation improves skills, but should not completely replace interaction with real patients, and it is emphasized that it does not fully address the biopsychosocial complexity of the patient. Simulation is suggested as a complementary, not a substitute, tool in nursing training.